Antimicrobial Sensitivity Pattern of Bacterial Pathogens Associated with Urinary Tract Infection - Akhtar, Nayareen; Rahman, Rezwanur; Sultana, Shahin; Rahman, Md Rezwanur (Delta Medical College Journal, 2017)
Correction: On 10th August 2017 due to typographical errors, the period of the study was changed from May 2016 to June 2017 and the caption of the red segment in Figure 1 was changed from No UTI, 41% to UTI, 59% Background: Urinary tract infection (UTI) is one of the common bacterial infections in mankind. The changing antimicrobial sensitivity in UTI demands use of appropriate antibiotics. Objective: This study was conducted to determine the distribution and antimicrobial susceptibility of uropathogens. Materials and method: This was a prospective study conducted in Bangladesh Medical College & Hospital, Dhaka, Bangladesh between May 2016 and June 2017 to identify the organisms causing UTI and their antibiotic susceptibility. Clean catch midstream urine samples were collected from 95 patients presenting with symptoms of UTI. Antimicrobial susceptibility was performed by disc diffusion method. Results: Out of 95 urine samples, 56 (58.9%) were found positive. The prevalence was significantly higher in females than in males (females: 58.9%; males: 41%). Age group of >48 years showed higher prevalence of UTI. The most common organisms isolated were Escherichia coli, Klebsiella, Pseudomonas, Proteus and Staphylococcus aureus. These represented 44.6%, 21.4%, 14.3%, 12.5%, and 7.14% of isolates respectively. Imipenem and Meropenem were found the most susceptible drug against isolated uropathogens. Conclusion: Most powerful antibiotics in our study were imipenem and meropenem. In conclusion, one can truly affirm that the choice of drugs in the treatment of UTI is becoming quite narrow today due to the wide scale resistance that the common UTI pathogens show to drugs which have been used previously. Delta Med Col J. Jul 2017 5(2): 57-62